Thermal characteristics and operation efficiency of solid-state electro thermal storage. (November 2021) - Khimenko, Aleksei V.; Tikhomirov, Dmitry A.; Kuzmichev, Aleksey V.; Trunov, Stanislav S.; Shepovalova, Olga V.
Abstract: This work is dedicated to studying characteristics of proposed dynamic-type electro-thermal storages (ETS). Experimental (laboratory) studies of thermal status of magnesium oxide heat-storage cells of conventional design with two slot-shaped channels and chamotte heat-storage cells with two round-shaped channels, in the modes of heat charging and heat emission of ETS have been carried out. Results of experiments on temperature change of electro-thermal storage units and that of heated air in ETS, for a number of reference points, in operating modes of charging and heat emission were applied in calculations of thermal characteristics of ETS including average value of heat-transfer coefficient of ETS external surface, average value of heat-transfer coefficient, in air channels of heat-storage units of ETS, aggregate value of ETS heat emission, quantity of heat accumulated in ETS, in absolute and relative units, average rates of heating and cooling of heat-storage units, in charging and heat emission operating modes of ETS. The efficiency of operation of standard magnesium oxide ETS with heat-storage cells having slot-shaped channels and chamotte ETS with heat-storage cells having round-shaped channels has been estimated. The developed design of chamotte ETS with heat-storage cells having round-shaped channels makes it possible to increase heat emission in channels of heat-storage cells by 15 % and to reduce the final cost of ETS by, at least, 15 % compared to existing devices. Mass-scale implementation of electro-thermal storage systems for heat supply in rural areas and farmer enterprises will make it possible to reduce power loss in networks, to normalize the daily load curve in power network and to improve regional environmental situation. Application of ETS in combination with power installations based on renewable energy sources (such as wind and solar installations) is considered to be perspective solution, as well.